REALIZATION OF SPEECH FUNCTIONS BY PRIMARY SCHOOL LEARNERS OF ENGLISH AS A FOREIGN LANGUAGE - Yusnita Sylvia Ningrum (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2007)
English learning in Indonesia share the same central characteristics of foreign language learning which lies in the amount and type of exposure to the language: there will be very little experience of the language outside the classroom, and encounters with the language will be through several hours of teaching in a school week. This paper as a result of a research describing the way the young learners negotiate meanings through their choices of speech functions and the realization of those speech functions through the choices of mood after they are being treated at school. The corpus of the data of this research is a stretch of approximately sixty-minutes dialogue between 5 primary school children and their teacher; the speech functions are categorized based on the Speech Function Network developed by Eggins and Slade (1997). It is found that children learning English as a foreign language can perform similar speech functions as adult in their spoken interaction. With the support from adult (teacher) and the proper environment, children whose native language is Indonesian and started to learn English when they were at school ages are able to interact with others, convey message and share ideas using English. They can also realize the speech functions into an organized and logical system of mood.